Legal Awareness and Community Participation in Village Development Planning in Plakaran Village, District Grumpy Sampang Regency - Saifuddin; Ansori; Mukhlis; Jufri, Muwaffiq; Boemiya, Helmy (GoAcademica Research & Publishing, 2024)
Village development is the implementation of the ideals of the Indonesian state to improve the welfare of village communities. In order to carry out village development so that it can run well, regularly and effectively, it must be done by first making a village development plan. In carrying out village development planning, village communities must be involved. The focus of the research is Legal Awareness and Community Participation in Village Development Planning in Plakaran Village, District Grumpy Sampang Regency, using social and legal research methods, while the results of this research are that the implementation of village development in Plakaran village does not fully involve the community, whereas community involvement will provide new values ​​and new ideas that are in accordance with community needs, so with community involvement in planning to implementation of village development will provide legal awareness to the community so that they can work together to build a better village.